Determining the Factors that Influence Online Purchase Intentions at Shopee Indonesia with Trust as Mediation - Solihin, Dede; Ahyani, Ahyani (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: This research was conducted to determine the factors that influence online purchasing intentions at Shopee Indonesia with Trust as Mediation.Methodology: This research uses quantitative methods with a casual design. The population in this research is all Shopee users in South Tangerang. The sampling technique used a purposive sampling method with a sample size of 120 people. Data was collected using a questionnaire and then analyzed using statistical tests using the SEM (Structural Equation Modeling) method using PLS 3.0 software.Finding: The research results show that perceived usefulness, Perceived Ease, and perceived risk have a significant effect on trust. Trust has a significant effect on Purchase Intention. Perceived usefulness has a significant effect on purchase intention. Perceived Ease does not have a significant effect on Purchase Intention. Risk Perceived has a significant effect on Purchase Intention. Trust has not been able to mediate the influence between Perceived Usefulness on Purchase Intentions. Trust can mediate the influence of Perceived Ease of Convenience on Purchase Intentions. Trust has not been able to mediate the influence between Risk Perceived on Purchase Intentions.Conclusion: The Trust variable has not been able to mediate the relationship between Perceived Usefulness and Perceived Risk on Purchase Intentions, however, the Trust variable can mediate the relationship between Perceived Ease on Purchase Intentions. Perceived Ease does not have a significant effect on Purchase Intention. Thus, to minimize the risks that occur when shopping online, companies must be able to maintain and increase consumer confidence in online transactions.